수요응답형 교통수단 스케줄링 알고리즘의 시각적 분석 - 김동규(Dongkyu Kim); 신동화(DongHwa Shin) (디지털콘텐츠학회논문지, 2024)
수요응답형 교통체계(DRT)는 기존 대중교통 시스템의 한계를 보완하며 교통 사각지대 문제를 해결하는 데 중요한 역할을 하고 있다. DRT의 효과적 운영을 위해서는 승객들의 요청에 대해 어떤 DRT 차량을 배정해야 하는지에 대한 결정을 최적화하는 것이 중요하다. 많은 연구자가 이러한 DRT 시스템의 스케줄링을 연구하고 있지만, 알고리즘의 수행 과정을 효과적으로 이해, 분석하기 위한 도구는 부재하다. 본 연구는 이러한 DRT 시스템의 스케줄링 알고리즘 연구자가 알고리즘 수행 과정을 탐색적으로 분석할 수 있도록 하는 대화형 시각화 시스템을 제안한다. 이 시스템은 승객 요청 분포, 교통 네트워크, 그리고 스케줄링 알고리즘 수행 과정을 확인할 수 있는 시각화 모듈로 이루어져 있으며, 상호작용 기법을 통해 연구자들이 알고리즘 수행 과정을 능동적으로 탐색할 수 있도록 한다. 제안하는 시스템에 대한 평가로서, 시스템을 활용하여 알아낼 수 있었던 스케줄링 알고리즘 분석 결과들을 밝힌다. Demand-responsive transport (DRT) systems address the limitations of traditional public transportation and play a key role in solving mobility challenges in underserved areas. Efficient DRT operations rely on optimizing vehicle-assignment decisions in response to passenger requests. Although considerable research has been conducted on DRT scheduling, tools for effectively understanding and analyzing the execution processes of these algorithm are lacking. Therefore, this study proposes an interactive visualization system that allows researchers to explore and analyze DRT scheduling algorithms. It includes visualization modules for passenger-request distribution, the transportation network, and algorithm execution. These interactive features can allow researchers to actively investigate the DRT scheduling process. Additionally, experimental evaluations of the proposed system demonstrate its effectiveness in providing key insights into DRT scheduling algorithms. KCI Citation Count: 0